Habitat suitability modelling of Rhacophorus reinwardtii (Schlegel, 1840) in Java, with notes on habitat characteristics from Malang, East Java - Kurniawan, Nia; Fathoni, Muhammad; Assiddiqy, Miftah Farid; Septiadi, Luhur; Rijalullah, Muhammad Asyraf (Journal of Tropical Biodiversity and Biotechnology, 2024)
The distribution of the Reinwardt's Gliding Frog, Rhacophorus reinwardtii (Schlegel, 1840), was recently thought to be restricted in Java. Furthermore, the constant and rapid deforestation in Java highlight the significance of the frog's habitat requirements in establishing the accurate species' conservation status. This study aims to predict the suitable habitat for this species in Java and to identify the habitat characteristics in Malang Region-East Java. Using the Maximum Entropy (MaxEnt) approach, we modelled the distribution of species and examined numerous types of breeding sites in Malang Region. Our findings revealed that the species inhabits a much more restricted and fragmented habitat in Java, where it inhabits both forest and agroforestry areas.